433PProspective outcomes of adolescent and young adult (AYA) patients received treatment from a tertiary cancer hospital in Bangladesh. (24th November 2019) - Khan, A A M; Islam, M R; Sumon, M A; Alam, M J; Hasan, A T M K
Abstract: Background: Malignancies in AYAs are increasing with increasing their death occurrences but a few data from developing countries. There are 72006601(44.2%) people under 15-39 years age group in Bangladesh. They are in vital age group not only for their own development but also for their country and for the world. This study was aimed to find out the outcome of treatment and causes of death. Methods: The study was an observational study. All cancer patients aged 15-39 years completed treatment at medical oncology department in National Institute of Cancer Research and Hospital (NICRH) from Jan.2016 to Dec.2017(24 months). Of them 593 patients were included for the study. Their follow up were taken over phone or departmental follow up registries up to May 2019. Information was prospectively studied. Results: Total 593 patients were enrolled for this study, male(M) 295(49.75%), female(F)298(50.25%) and M:F=1:1.01. After follow up, found 170(28.67%) patients were untraceable whose 63(10.62%) patients had no contact number. Among the remaining 473 patients 170(35.94%) were died due to anorexia 162(95.3%), both nausea and vomiting 90(53%), pain and fever 65(38.24%), diarrhea 57(33.53%), respiratory distress 38(22.35%), cachexia 37(21.76%), bleeding and generalized swelling 18(10.60%), opportunistic infection 10(5.88%), stroke 3(1.176%), surgical complication 2(1.18%). Of the died patients male were 96, female were 74 and M:F was 1.3:1. The leading causes of death, according to specific disease, were lung cancer 11(61%), head neck cancer 12(57%), sarcoma 56(46%), GIT(gastrointestinal tract) cancer 39(40.63%) and leukemia 12(35%). Least death occurred in GCT (germ cell tumor) 1(4.34%) and lymphoma 7(9%). Alive patients were 240. Of them male were 84, female were 156 and the ratio was M:F=1:1.86. According to specific disease, the highest survival were in testicular malignancy 18(85.71%), breast cancer 88(71%), FGT (female genital tract) 26(70%), lymphoma 44(59%) and GIT malignancy42(43.75%). Conclusions: Death occurrences were 170(35.94%) and tract out of follow up were 170(28.67%) in AYA that were dangerously alarming for developing countries as youth are majority of total population in developing countries. Legal entity responsible for the study: Abdullah Al Mamun Khan. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.